Determining accuracy of bill of materials for a surface mount technology machine using solidworks software - Chong, Siaw Hua (2009)
Bill of Materials (BOM) is a simple list of the contents of subassembly or material to assembly a complete product. The BOM mainly use for the Material Requirement Planning (MRP) to determine the inventory level should be ke!ep for production. Costing is done base on the BOM to set the total cost for the product. BOM is part of the important list for the production to determine what part, quantity part to be used and as reference with the engineering drawing to do the assembly of the product or machine. In this project, an investigation has been done in a contract manufacturing company which received BOM from Original Equipment Manufacturer. In order to verify the BOM, all the engineering drawing been modeling in 3d format. Process of assembly of the part been done by using Solidworks software. Auto generated BOM from the software has been compared with the Original provide by the OEM. Analysis to determine accuracy of the BOM has been done and Discussion on the reason of the discrepancy has been identified. However, some of the part not been verified as the restriction of the Company Policy